Botany for the artist - Simblet, Sarah; Scott-Hunter, Sam.; Harris, Stephen (New York : DK Pub., 2010)
Provides step-by-step instructions for drawing realistic plants, trees, and flowers.
-- The art of botany -- Drawing plants -- Diversity -- Roots -- Stems -- Leaves -- Flowers -- Fruit, cones, and seeds.
Includes index.
"Featuring plants from the University of Oxford Botanic Garden and Oxford University Herbaria".
Keywords: Botanical illustration -- Technique; Plants in art